2012
DOI: 10.1542/peds.2012-0900d
|View full text |Cite
|
Sign up to set email alerts
|

Use of Psychotropic Medication in Children and Adolescents With Autism Spectrum Disorders

Abstract: OBJECTIVES: The goal of this study was to examine rates of psychotropic medication use and identify associated child and family characteristics among children and adolescents with autism spectrum disorder (ASD) enrolled in an autism registry maintained by the Autism Treatment Network (ATN). METHODS:The sample, derived from the ATN registry, consists of 2853 children aged 2 to 17 years with diagnoses of ASD supported by Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, and the Autism Diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
104
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 30 publications
9
104
4
Order By: Relevance
“…Our findings are consistent with, but slightly higher than, previously reported rates based on Medicaid claims data 7 or parental report 11,12 for similarly aged samples of children with ASD. Our increased rates may reflect the longer time periods over which many of our study subjects were observed (.3 years on average compared with 1 year or a single point in time in other studies).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are consistent with, but slightly higher than, previously reported rates based on Medicaid claims data 7 or parental report 11,12 for similarly aged samples of children with ASD. Our increased rates may reflect the longer time periods over which many of our study subjects were observed (.3 years on average compared with 1 year or a single point in time in other studies).…”
Section: Discussionsupporting
confidence: 90%
“…The appropriate reasons and indications for antipsychotic medications and antidepressants, however, are less clearly defined; these medications could have been given for a wide variety of symptoms among children with ASD, 13 without proven benefit or safety. 22 Although older age was significantly associated with both psychotropic use and polypharmacy, consistent with the literature, 7,11,12 polypharmacy was still significant among the younger age groups (33% of children aged 2-10 years and 10% of 0-to 1-year-olds) for whom safety concerns are increased and evidence of benefit even more sparse. [23][24][25] Also in keeping with findings described in the literature, 11 children from the southern region were significantly more likely than children from the northeast and west to be multiclass polypharmacy users, raising questions about the availability of nonpharmacologic, behaviorally based services and treatments in the south, where other health outcomes and health care services have been found to be poorer than in other parts of the country.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Reported rates of use among children with ASD have ranged from 27% to 83%, with polypharmacy ranging from 10% to 20%. [6][7][8][9][10][11][12] The rates reported to date have either been based on a fairly limited time period (1 year) or reflect a single point in time and therefore do not yield information about the chronic use of psychotropic medications. Furthermore, all previous studies about psychotropic use and related factors for children who are commercially insured (who comprise the majority of children in the United States 16 ) have been based on parental report and included relatively small sample sizes (from 326 to 5181).…”
mentioning
confidence: 99%
“…T he use of psychotropic medications as one component of treatment for children with autism spectrum disorder (ASD) has grown rapidly, with surveys indicating that * 50% of individuals with ASD take psychotropic drugs or supplements intended to address impairing behaviors (Aman et al 2005b;Coury et al 2012). Whereas much use of psychotropic agents in ASD is off label and guided by limited empirical evidence, two agents have United States Food and Drug Administration (FDA) indications for serious behavior problems in children with autistic disorder.…”
Section: Introductionmentioning
confidence: 99%